Numerical Simulation on Steam Gasification of a Single Biomass Char Particle. (May 2017) - Guo, Li; Zhai, Ming; Zheng, Yan; Dong, Peng
Abstract: The study of biomass char gasification has become a research focus due to the advantages such as clean, efficient, product gas with higher heating value and so on. The paper established a steam gasification model of a single char particle by making an in-depth theoretical research on biomass char. Numerical simulation results were compared with the experiments in literature and the primary effects on gasification were analyzed. The results are obtained that reducing the diameter of the biomass char particle, increasing the gasification temperature and the pressure of H2 O are beneficial to the conversion and the higher heating value of the product gas.